Caseous Lymphadenitis In Goats: First Report Of Two Clinical Cases From Punjab (India) (Applied Biological Research, 2013)
Caseous lymphadenitis is a sporadic bacterial disease of chronic suppurative lymphadenitis in both  sheep and goats. The disease is caused by Corynbacterium pseudotuberculosis, a Gram positive rod  which generally appears coccoid. The disease is manifested by local inflammation at the site of  bacterial entrance, and abscessation of both internal and external lymph nodes (Glen, 2000). Goats are  more prone to the external abscesses while sheep are more prone to internal abscesses (Baird and  Fontaine, 2007). Internal abscesses are detectable only at necropsy. It is the internal abscesses that are  fatal, whereas external abscesses are generally responsible for disease transmission (Ivanovic et al., 2009).
Keywords: Lymphadenitis; Goats; Clinical; Punjab